The AraC Negative Regulator family modulates the activity of histone-like proteins in pathogenic bacteria. - Araceli E Santiago; Michael B Yan; Tracy H Hazen; Brooke Sauder; Mario Meza-Segura; Mario Meza-Segura; David A Rasko; Melissa M Kendall; Fernando Ruiz-Perez; James P Nataro (PLoS Pathogens, 2017)
The AraC Negative Regulators (ANR) comprise a large family of virulence regulators distributed among diverse clinically important Gram-negative pathogens, including Vibrio spp., Salmonella spp., Shigella spp., Yersinia spp., Citrobacter spp., and pathogenic E. coli strains. We have previously reported broad effects of the ANR members on regulators of the AraC/XylS family. Here, we interrogate possible broader effects of the ANR members on the bacterial transcriptome. Our studies focused on Aar (AggR-activated regulator), an ANR family archetype in enteroaggregative E. coli (EAEC) isolate 042. Transcriptome analysis of EAEC strain 042, 042aar and 042aar(pAar) identified more than 200 genes that were differentially expressed (+/- 1.5 fold, p<0.05). Most of those genes are located on the bacterial chromosome (195 genes, 92.85%), and are associated with regulation, transport, metabolism, and pathogenesis, based on the predicted annotation; a considerable number of Aar-regulated genes encoded for hypothetical proteins (46 genes, 21.9%) and regulatory proteins (25, 11.9%). Notably, the transcriptional expression of three histone-like regulators, H-NS (orf1292), H-NS homolog (orf2834) and StpA, was down-regulated in the absence of aar and may explain some of the effects of Aar on gene expression. By employing a bacterial two-hybrid system, LacZ reporter assays, pull-down and electrophoretic mobility shift assay (EMSA) analysis, we demonstrated that Aar binds directly to H-NS and modulates H-NS-induced gene silencing. Importantly, Aar was highly expressed in the mouse intestinal tract and was found to be necessary for maximal H-NS expression. In conclusion, this work further extends our knowledge of genes under the control of Aar and its biological relevance in vivo.